Ectopic Cushing Syndrome: A Diagnostic and Therapeutic Challenge: Síndrome de Cushing Ectópica: Um Desafio Diagnóstico e Terapêutico - Fernandes, Vera; Monteiro, Ana Margarida; Santos, Maria Joana; Pereira, Maria Lopes; Marques, Olinda (Gazeta Médica, 2018)
INTRODUCTION: Ectopic Cushing syndrome is a rare disease and the identification of the adrenocorticotropic hormone (ACTH) producing tumour may occur years after Cushing syndrome diagnosis, hampering the therapeutic management of these patients. CASE REPORT: A 78-year-old woman was referred to the Endocrinology department due to Cushing syndrome. She had signs and symptoms of hypercortisolism and the clinical investigation showed a dependent ACTH Cushing syndrome with a nor-mal pituitary magnetic resonance imaging, negative catheterization of the petrosal sinuses and an 8 mm pulmonary nodule. Scintigraphy with somatostatin receptors, PET-68Ga-SRP, (bronchofibroscopy) and bronchial aspirate cytology were normal. Due to clinical worsening, she started on metyrapone with a very favourable clinical and analytical response. DISCUSSION: This clinical case was a diagnostic and therapeutic challenge. Although the location of the primary tumour was not found, control of hypercortisolism was achieved, improving the patient’s quality of life.